Use of intravaginal devices with progesterone in beef heifers: effect of the time range in which fixed timed artificial insemination is performed - Monteserin, Jorge (2018)
In the study was used 333 15-month-old beef heifers with body condition of 6 on average (scale 1-9). On this, 53.5% presented an active corpus luteum at the beginning of the study. On day 0, an intravaginal device with 0.5 g of progesterone (IVD) was placed and 2 mg of estradiol benzoate was injected. On day 8 the IVD was removed and 0.5 mg of cloprostenol and 0.5 mg of estradiol cypionate were i.m. injected. On day 10, artificial insemination at fixed time (IATF) was carried out, distributing the animals at random to be inseminated in three-time ranges: I) 48-50 h; II: >50-53 h; III) >53-56 h. Frozen semen in 0.5 ml straws was used. Pregnancy diagnosis was performed by ultrasound at 30 days post- IATF. Two animals lost the DISP and were excluded from the analysis. There was no effect on pregnancy rate of the time range in which the IATF was performed after the DISP was removed (I: 64.0%, II: 69.8%, III: 66.9%). It is concluded that in beef heifers using the ovulation synchronization protocol of the study, the IATF can be performed between 48 and 56 h after the removal of the device without affecting the pregnancy rate.